Microwave Electromagnetic Processing of Ni0.1 Zn 0.9 Fe2O4 for Absorbent Electronics - Kumar Saurav (Journal of Electronic Design Engineering, 2023)
Ni0.1 Zn 0.9 Fe2O4 pellets were prepared for microwave heat exchanger by sintering method. The effects of ZnO content by weight percentage and soaking period, microstructural, and electrical and microwave absorption properties and diffusivity were studied by a network analyzer and scanning electron techniques. The discharged thermal energy encourages the growth and sintering of particles due to their dissemination pressurized processes. The amount of the discharged heat and the number of aerosolized products expected on the Electronics features of ZnO including the type of functional group, and modular formation of the material.